O discurso especista em um projeto de lei sobre o Direito Animal - Pinheiro, Letícia Nascimento Alvarenga (2022)
This thesis examines the functioning of the speciesist discourse in discursive practices surrounding a bill about Animal Rights in the Brazilian legislative field. We aim to identify the discursive positioning that cross the referred bil and identify the social and discursive space of antagonistic positioning to the animal cause. Therefore, we employed the theoreticalmethodological of French Discourse Analysis framework (DA), in its enunciative-discursive perspective, more specifically, the one practiced by Maingueneau (1997, 2007, 2008a, 2008b, 2013, 2015a, 2015b). We mobilized the notions of interdiscursive competence and interdiscourse and the categories of discursive positioning and social/discursive space, proposed by this author. In this regard, we articulate the discourses that emerge from and in the discursive practices surrounding the bill, with the purpose of revealing which positioning are enrolled in the condition of antagonist of the animal cause. We also discuss, in dialogue with the philosophers Honneth (2003, 2018), Singer (2018, 2020) and Regan (1983, 2005), a conception of ethics that clarifies the problem of the moral status of non-human animals. It has base on a proposition of qualitative-interpretative research of an analytical nature. The results reveal that, within the argumentative evolution in the legislative field, there is a preponderance of a speciesist paradigm in the treatment of non-human animals by our society, from which crossings of a mainly economic order arise. In effect, we were also able to highlight enunciative positioning enrolled in such a paradoxical way, which mark the absence of any elementary recognition with non-human animals, as evidence of a relationship sustained on the basis of a system of conviction that denatures the recognition of the other.